KINERJA PENGERING PAKAIAN DENGAN MEDIA AIR PANAS MENGGUNAKAN ALAT PENUKAR KALOR BERBAHAN TEMBAGA - Yudi Setiawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2020)
Abstrac Tirta Tapta Pemali Hot Spring which is one of the natural tourism assets in the village of Pemali, Pemali Regency, about 20 km from Sungailiat City. One source of energy that can be used to dry clothes in Pemali attractions is a natural hot spring, while the volume of air that comes out increases. Clothes dryer is a device / machine that functions to dry clothes with certain heat sources. This research makes clothes dryer is a model (prototype) tool / machine that uses a heat source with the same temperature as the temperature of the hot air baths. The hot water used is likened to hot air in the Tirta Tapta Pemali bath, which is around ± 40oC. Research carried out by flowing hot air into the copper pipe in the drying chamber, the heat generated will be driven by the wind from the blower to be used. Variations in this study are the flow of water of 2.4 - 3 liters / minute, 5.4 - 6 liters / minute, and 10.9 - 11.5 liters / minute. The parameters issued are how much the mass of clothing and the temperature in the drying room every 5 minutes. 7 pieces of clothing, namely 293.3 minutes with water discharge 10.9 -11.5 liters / minute with the highest average room temperature of 42.33 oC Keywords : dryer, hot water, copper